Legalitas Abortus Provocatus Sebagai Akibat Tindakan Pemerkosaan - Ida Bagus Wirya Dharma (Fakultas Hukum, Universitas Warmadewa, 2022)
Abortus Provocatus become legal issues that always have pros and cons. Pros group basically not directly support the abortion however more emphasize on the importance to protect reproductive rights that having by woman and the guarantee of the children’s future life. Cons group by emphasize the right of life that having by the fetus as human that has right to life. The data showed that abortion can be done with some reasons, one of them is pregnant as the result of the rape. This study aimed to analyze juridically the legality of abortus provocatus as the effect of the rape. The research method used was normative legal research by putting law as norm with statutory regulations and doctrinal approaches. The legality of Abortus Provocatus as the result of the rape can be done, it is on Article 75 paragraph (3), Article 75 paragraph (4), Article 126 paragraph (4), and Article 127 paragraph (2) Statutory number 36 Year 2009 regarding Healthy and Article 31, Article 34, Article 35 Government Regulation Nomor 61 Year 2014 regarding Reproduction Health.